ANALISIS MANFAAT STRATEGI MARKETING MIX 7P TERHADAP CITRA MERK TEH BUTONG DI PTPN NUSANTARA IV BAH BUTONG: ANALISIS MANFAAT STRATEGI MARKETING MIX 7P TERHADAP CITRA MERK TEH BUTONG DI PTPN NUSANTARA IV BAH BUTONG - Eka Putra, Salsadilla; Nurmala Sari , Tika; Simatupang, Jumeida; Murtani, Alim; Tanjung, Yahya (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2025)
The competition in the tea beverage industry in Indonesia is getting tighter along with the increasing number of brands and the variety of products offered to consumers. This condition requires every company to have the right marketing strategy in order to be able to maintain its existence while building a strong brand image in the minds of consumers. One of the most widely used approaches in modern marketing strategies is the 7P marketing mix which includes products, prices, venues, promotions, people, processes, and physical evidence. This research analyzes the benefits of implementing the 7P marketing mix strategy (Product, Price, Place, Promotion, Process, People, Physical Evidence) on the brand image of Butong Tea produced by PTPN IV Bah Butong. The research method uses a quantitative approach with a survey method. The population is all consumers of PTPN Nusantara Butong Tea with a sample sampling technique using non-probability sampling with purposive sampling.   The research results show that each 7P element contributes positively to improving brand image. Quality products, competitive prices, wide distribution, creative promotions, structured operational processes, skilled human resources, and an attractive physical appearance play an important role in strengthening a brand. This strategy creates a strong relationship with consumers and increases the brand's competitiveness in the market. From the data I got after I conducted interviews with approximately 30 respondents, there are still many who don't know about Butong Tea, this is because Butong tea factories market their products more overseas, such as Malaysia, Singapore and other countries.The implications of the research results provide a basis for consideration for the management of PTPN Nusantara IV and related stakeholders in developing brand-based plantation product marketing policies